Error Analysis Made By The Students’ Fifth Semester of HKBP Nommensen University In Writing Explanation Text - Anita Theresia Br Saragi; Sahlan Tampubolon; Rina Octavia Simarmata; Juliaster Marbun (Journal on Education, 2023)
The purpose of this study is to find out students' mistakes in writing explanatory text. For that the researcher will look at the results of student writing. The researcher wants to know what mistakes students make when writing explanatory texts and how these types of errors affect students' abilities in writing explanation texts. This research is qualitative in nature. Interviews were conducted to support the data obtained from students' answers to writing tests about explanatory texts. Interviews were used to find out the circumstances that led to student errors, and written tests were used to measure each student's learning level. As many as 32 fifth semester HKBP students from Nommensen University Medan took part. Based on student experiences, data analysis determines which types of errors are more common than the data. From the results of the written test, the authors found 119 data errors. There were 44 omission category errors made by 22 students; 29 errors in the addition category were made by 17 students; 24 errors in the misformation category were made by 11 students; 16 mistakes in the wrong misordering category were made by 13 students; 2 errors in the archive forms category were made by 2 students; 4 mistakes in the alternating form category were made by 3 students. Errors in student writing are caused by the following: Grammatical and vocabulary errors.